Astrophysics for physicists - Choudhuri, Arnab Rai (New Delhi Cambridge University Press, 2010)
Designed for teaching astrophysics to physics students at advanced undergraduate or beginning graduate level, this textbook also provides an overview of astrophysics for astrophysics graduate students, before they delve into more specialized volumes. Assu
Keywords: Astrophysics; Science; Astronomy